STRATEGI PAI DALAM MEMBENTUK KEMBALI AKHLAK SISWA/I KELAS XII PASCA COVID-19 DI SMK 1 ROKITA SARI BANGUN PURBA - Jailani, Muhammad; Nasution, Rika Safitri; Nurainun, Nurainun (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2023)
Covid-19 is an infectious disease virus that attacked the world in early 2020 until now. This virus has a very broad impact, including education. After Covid 19, the education system changed, all students carried out the learning process online through the Zoom application which was connected to the Internet, causing an moral crisis for students due to a lack of education, especially Islamic religious education in schools. Therefore, researchers conducted this research to examine Pai's Strategy in Reshaping the Morals of Class XII Students after Covid 19 at SMK 1 ROKITA Sari Bangun Purba. This study aims to reshape good character, ethics and morals in accordance with Islamic teachings. The strategy used is to provide exemplary or good examples, habituation, reprimands, advice, attention, and educational sanctions. The supporting factors as well as the inhibiting factors are family environment, school environment, community environment, student awareness, and electronic media. This type of research uses qualitative methods. Data collection techniques used in this study include: observation, interviews and documentation. The results of this study indicate that the Islamic Religious Education Strategy applied to students can work well, especially for class XII who have started to think and change their nature gradually. This strategy is also in line with theories related to morality, understanding, to the function and purpose of education, namely to form students who are ethical, moral and have good morals.